2001
DOI: 10.1200/jco.2001.19.1.183
|View full text |Cite
|
Sign up to set email alerts
|

Neuroblastoma With Symptomatic Spinal Cord Compression at Diagnosis: Treatment and Results With 76 Cases

Abstract: Radiotherapy, laminectomy, and chemotherapy showed comparable ability to relieve or improve SCC. However, patients treated with chemotherapy usually did not require additional therapy, whereas patients treated either with radiotherapy or laminectomy commonly did. No patient presenting with (or developing) severe motor deficit recovered or improved. Sequelae were documented in 44% of surviving patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
87
1
14

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(119 citation statements)
references
References 18 publications
12
87
1
14
Order By: Relevance
“…Five patients with intraspinal masses presented with new symptoms, including scoliosis. De Bernardi et al (24) have reported 40% of survivors of neuroblastoma with spinal cord compression developed late effects, such as scoliosis and sphincteric deficit. Therefore, patients with residual tumors, especially with intraspinal masses, require long-term follow-up.…”
Section: A At Diagnosismentioning
confidence: 99%
“…Five patients with intraspinal masses presented with new symptoms, including scoliosis. De Bernardi et al (24) have reported 40% of survivors of neuroblastoma with spinal cord compression developed late effects, such as scoliosis and sphincteric deficit. Therefore, patients with residual tumors, especially with intraspinal masses, require long-term follow-up.…”
Section: A At Diagnosismentioning
confidence: 99%
“…However, the difference was not statistically significant, and analysis of other prognostic factors was not attempted. In children with newly diagnosed neuroblastoma and SCC, chemotherapy may also be the preferred primary treatment, although there is controversy in the literature [45].…”
Section: The Role Of Chemotherapymentioning
confidence: 99%
“…Chemotherapy may have a role in treating SCC caused by chemosensitive tumors, such as lymphomas [38][39][40][41], leukemia [22,42], germ cell tumors [43,44], and neuroblastoma [45], either in combination with other treatment modalities or on its own. The possibility of using chemotherapy as the primary treatment for SCC in patients with chemosensitive tumors is attractive, as it would avoid the potential morbidity of surgery and provide simultaneous treatment to other foci of systemic disease.…”
Section: The Role Of Chemotherapymentioning
confidence: 99%
“…4). Así como en los adultos se consideran distintas opciones terapéuticas, en los niños la primera opción de tratamiento, aparte del tratamiento médico con esteroides, es la administración de quimioterapia ofreciendo la cirugía (laminectomía) en situaciones de inestabilidad ósea y la radioterapia 26,27 en aquellos tumores considerados radiosensibles por las posibles secuelas óseas de ambos tratamientos. Los resultados describen un control del dolor en un 70% (similar en los adultos) con mejoría de la función motora hasta en un 45-60 % (muy superior a la de los adultos donde la incapacidad previa para deambular condiciona los resultados).…”
Section: Síndrome De Compresión Medularunclassified